2014
DOI: 10.1590/0037-8682-0239-2013
|View full text |Cite
|
Sign up to set email alerts
|

Composition, abundance and aspects of temporal variation in the distribution of Anopheles species in an area of Eastern Amazonia

Abstract: Introduction:The diverse and complex environmental conditions of the Amazon Basin favor the breeding and development of Anopheles species. This study aimed to describe the composition, abundance and temporal frequency of Anopheles species and to correlate these factors with precipitation, temperature and relative humidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
(44 reference statements)
0
7
1
Order By: Relevance
“…Considering the environmental variables, a strong correlation was observed between An. darlingi and relative humidity of the air (R. H%) (r 2 > 0.5), differing from the data found by Barbosa et al (2014), where this species showed no correlation with temperature and humidity, in a study on the composition and temporal variation of anophelines, in the state of Macapá, northern Brazil.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Considering the environmental variables, a strong correlation was observed between An. darlingi and relative humidity of the air (R. H%) (r 2 > 0.5), differing from the data found by Barbosa et al (2014), where this species showed no correlation with temperature and humidity, in a study on the composition and temporal variation of anophelines, in the state of Macapá, northern Brazil.…”
Section: Discussioncontrasting
confidence: 66%
“…In the Brazilian Amazon, the temporal distribution of anophelines populations varies according to the region due to the extensive territorial area and the high diversity of habitats that make up the biome. In the state of Amapá, located in the eastern Amazon, Barbosa et al (2014) observed the unimodal temporal distribution of An. darlingi, differing from the data obtained in this study.…”
Section: Discussionmentioning
confidence: 90%
“…However, studies conducted in peri-urban areas of the city of Macapá, in the state of Amapá, Brazil, demonstrated that it can be a significant regional vector [9][10][11] as well as in Boa Vista, in the state of Roraima [12]. Supporting these findings, in the District of Coração, state of Amapá, A. marajoara was the most frequent species, together with A. darlingi and A. braziliensis, showing anthropophilic behavior and being captured in both indoor and outdoor environments [13,14].…”
Section: Introductionmentioning
confidence: 65%
“…(2009) found a significant correlation between A. darlingi and the rainy season. Other reports have shown relevant densities for these vectors in Amazonian regions wettest periods (taDei et al 1998;moutinHo et al 2011;BarBosa et al 2014) and the island of São Luiz (Xavier & reBêlo 1999). In the rainy season, the availability of natural breeding sites increases, providing new breeding sites for anophelines, a hegemonic factor for expanding the densities of these mosquitoes.…”
Section: Discussionmentioning
confidence: 97%
“…The studies of malaria vectors are relevant for the biology knowledge, the behavior of species and the dynamic transmission of plasmodia parasites in each locality, helping in this way to elucidate the disease chain, the prediction of outbreaks and the guidance of control actions (BarBosa et al 2014(BarBosa et al , 2016. The entomological parameters such as density, anthropophilia, zoophilia, peaks of hematophagic activity, seasonal variations, infection rate and blood-feeding patterns are among the most frequent for the determination of the vector species (BarBosa et al 2014).…”
mentioning
confidence: 99%